A DFT study of quantum electronic transport properties of InTeCl - Batool, Hira; Majid, Abdul; Alkhedher, Mohammad; Bulut, Niyazi; Al-Adwan, Ibrahim (Elsevier Sci Ltd, 2023)
This work is carried out to investigate the structural, electronic and transport properties of InTeCl in bulk and slab periodicities using Density Functional Theory (DFT). The analysis of the structural parameters including bond length, lattice constants and bond angles of the materials was carried out in detail. The band gap of the material for the bulk and monolayer was found as 1.57 eV and 1.33 eV respectively. The direct to indirect transition of band gap is observed when the material is downscaled from bulk to the slab. Transport properties of the materials were computed using DFT based tight-binding method combined with non-equilibrium green functions (NEGF) formalism. The nano device Au-InTeCl-Au with fixed length of the central region was simulated to study IV-characteristics, transmission spectra and Hamiltonian states. Moreover, to check the diffusion properties of the material Nudged Elastic Band (NEB) calculations were carried out which revealed minimum transition barrier for bulk, slab and bilayer as 1.32 eV, 1.67 eV and 1.70 eV respectively. The current-voltage (IV) characteristic curves and transmission spectra for the materials were also studied to investigate the conductivity trend.
Keywords: Density functional theory; InTeCl; NEGF; NEB; Transport properties